Some categorical aspects of BCH-algebras - Muhammad Anwar Chaudhry; Hafiz Fakhar-ud-din (International Journal of Mathematics and Mathematical Sciences)
We show that the category BCH of BCH-algebras and BCH-homomorphisms is complete. We also show that it has coequalizers, kernel pairs, and an image factorization system. It is also proved that onto homomorphisms and coequalizers, and monomorphisms and one-to-one homomorphisms coincide, respectively, in BCH. It is shown that MBCI is a coreflexive subcategory of BCH. Regular homomorphisms have been defined and their properties are studied. An open problem has been posed.